Digital PCR Discriminates between SARS-CoV-2 Omicron Variants and Immune Escape Mutations - Steven C. Holland; LaRinda A. Holland; Matthew F. Smith; Mihyun B. Lee; James C. Hu; Efrem S. Lim (Microbiology Spectrum, 2023)
ABSTRACT As severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve, mutations arise that will allow the virus to evade immune defenses and therapeutics. Assays that can identify these mutations can be used to guide personalized patient treatment plans. Digital PCR (dPCR) is a fast and reliable complement to whole-genome sequencing that can be used to discriminate single nucleotide polymorphisms (SNPs) in template molecules. Here, we developed a panel of SARS-CoV-2 dPCR assays and demonstrate its applications for typing variant lineages and therapeutic monoclonal antibody resistance. We first designed multiplexed dPCR assays for SNPs located at residue 3395 in the orf1ab gene that differentiate the Delta, Omicron BA.1, and Omicron BA.2 lineages. We demonstrate their effectiveness on 596 clinical saliva specimens that were sequence verified using Illumina whole-genome sequencing. Next, we developed dPCR assays for spike mutations R346T, K444T, N460K, F486V, and F486S, which are associated with host immune evasion and reduced therapeutic monoclonal antibody efficacy. We demonstrate that these assays can be run individually or multiplexed to detect the presence of up to 4 SNPs in a single assay. We perform these dPCR assays on 81 clinical saliva SARS-CoV-2-positive specimens and properly identify mutations in Omicron subvariants BA.2.75.2, BM.1.1, BN.1, BF.7, BQ.1, BQ.1.1, and XBB. Thus, dPCR could serve as a useful tool to determine if clinical specimens contain therapeutically relevant mutations and inform patient treatment. IMPORTANCE Spike mutations in the SARS-CoV-2 genome confer resistance to therapeutic monoclonal antibodies. Authorization for treatment options is typically guided by general trends of variant prevalence. For example, bebtelovimab is no longer authorized for emergency use in the United States due to the increased prevalence of antibody-resistant BQ.1, BQ.1.1, and XBB Omicron subvariants. However, this blanket approach limits access to life-saving treatment options to patients who are otherwise infected with susceptible variants. Digital PCR assays targeting specific mutations can complement whole-genome sequencing approaches to genotype the virus. In this study, we demonstrate the proof of concept that dPCR can be used to type lineage defining and monoclonal antibody resistance-associated mutations in saliva specimens. These findings show that digital PCR could be used as a personalized diagnostic tool to guide individual patient treatment.